Opioid conversion ratios used in palliative care: is there an Australian consensus?. Issue 5 (May 2014) - Syrmis, W.; Good, P.; Wootton, J.; Spurling, G.
Abstract Background Opioid switching or rotation is reported to be a common practice in palliative care. Published tables of opioid conversion ratios have been found to vary in their recommendations, potentially leading to significant differences in clinical practice. Aims To identify common practices in the calculation of opioid equianalgesia by specialist palliative medicine practitioners and trainees. Method An anonymous, cross‐sectional, online survey completed by 85 Australian palliative care specialists or advanced trainees. Questions focused on conversion ratios used in switching between oral and parenteral opioid doses; conversion ratios used when switching from other opioids to oral morphine; and practice of commencing methadone. Results The majority of respondents calculated equianalgesic doses for morphine, oxycodone and hydromorphone using the same conversion ratios. Methadone was used almost equally as either the sole opioid or as a 'co‐opioid'. The majority surveyed converted slow‐release hydromorphone differently to the manufacturer's recommendations. Conclusion Further discussion among Australian palliative care specialist organisations is recommended in order to produce uniform conversion guidelines to improve consistency and safety in the prescribing of opioids.